Design and synthesis of a new fluorescent probe for cascade detection of Zn2+ and H2PO4− in water and targeted imaging of living cells. (14th March 2019) - Du, Kui; Liu, Jian; Shen, Runpu; Zhang, Pengfei
Abstract: Design and synthesis of new fluorescence probes with good water‐solubility is of great importance to better understanding the significant role of ions which are related to biology and the environment. As important ions, zinc ion (Zn 2+ ) and dihydrogen phosphate ion (H2 PO4 − ) display essential roles in living systems, and quantitative detection of these ions in water is still a challenge. In order to consider the significant role of the galactose moiety in the design of a water‐soluble fluorescence sensor, herein, we have developed a novel probe, Gal‐AQTF, for the cascade detection of Zn 2+ and H2 PO4 − with excellent selectivity in water. Through the introduction of the galactose moiety onto the sensor AQTF, which has been reported earlier by us, the water‐solubility, cell compatibility and targeting ability were enhanced. Gal‐AQTF has been successfully applied in the imaging of the living cells of HepG2 and A549, and illustrated good selectivity for the HepG2 cells which overly express the asialoglycoprotein (ASGP) receptor.